2018
DOI: 10.48550/arxiv.1810.12646
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Prosodic entrainment in dialog acts

Uwe D. Reichel,
Katalin Mády,
Jennifer Cole

Abstract: We examined prosodic entrainment in spoken dialogs separately for several dialog acts in cooperative and competitive games. Entrainment was measured for intonation features derived from a superpositional intonation stylization as well as for rhythm features. The found differences can be related to the cooperative or competitive nature of the game, as well as to dialog act properties as its intrinsic authority, supportiveness and distributional characteristics. In cooperative games dialog acts with a high autho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…However, it must be noted that not all speech acts in a naturalistic dialogue serve the same function, which means that dialogue act type may affect entrainment during the interaction. For example, Reichel, Mády and Cole (2018) found that people show a greater tendency to entrain during collaborative dialogue acts than during competitive ones. The way entrainment is affected by dialogue act type, social factors such as collaboration, and the interaction between the two requires further investigation, both in individuals with and without ASD.…”
Section: Discussionmentioning
confidence: 99%
“…However, it must be noted that not all speech acts in a naturalistic dialogue serve the same function, which means that dialogue act type may affect entrainment during the interaction. For example, Reichel, Mády and Cole (2018) found that people show a greater tendency to entrain during collaborative dialogue acts than during competitive ones. The way entrainment is affected by dialogue act type, social factors such as collaboration, and the interaction between the two requires further investigation, both in individuals with and without ASD.…”
Section: Discussionmentioning
confidence: 99%